The Economics of contemporary art markets, strategies and stardom - Zorloni, Alessia (Berlin Springer, 2013)
The book examines the contemporary art system with a broad and systematic approach, through the application of models of microeconomics and industrial organizations. By breaking down the traditional barriers between different academic disciplines such as art and economics, this book offers a unique opportunity to grasp the complexities of the contemporary art world and provides the tools to conduct a structural analysis of that market. The result is an in-depth analysis of the contemporary art market from an interdisciplinary perspective. While it is not a textbook in the strictest sense, the book offers a concise and effective overview of all actors in the art system, and provides supporting data and valuable information, both conceptual and practical. It is therefore a text that can be used by students wishing to better understand the complex dynamics that govern the contemporary art market, but also by cultural managers, collectors, potential art investors or simply art lovers who need a quick reference.​
Keywords: Art, Modern -- Prices; Art, Modern -- 21st century -- Economic aspects